The PUNISHMENTS FOR INTELLECTUAL ACTORS IN THE CRIME OF MURDER: COMPARATIVE STUDY OF ISLAMIC LAW AND POSITIVE LAW IN INDONESIA - Muhammad Hanifan Musliman Ma'as; Mohammad Syifa Amin Widigdo (Universitas Islam Negeri Mataram, 2023)
The involvement of intellectual actors in criminal cases generally goes unpunished and does not receive much attention in academic studies. Positive law in Indonesia and Islamic law have clear provisions regarding punishment for criminal acts committed by intellectual actors, especially in cases of murder. Therefore, the article aims to understand the position of intellectual actors in murder cases in Islamic law and positive law. In Islamic law, the intellectual actor could receive the death penalty. Similarly, in the positive law, the death penalty could also be applied to the intellectual actor of murder cases. This case of murder provides an important illustration of how Islamic law is, to a certain extent, accommodated in positive law in Indonesia. By examining primary and secondary sources on the issue of these intellectual actors in Islamic law (fiqh literature) and positive law (Kitab Undang-undang Hukum Pidana, KUHP), this article comparatively discusses the similarities and differences between Islamic law and positive law in providing legal opinion for intellectual actors in murder cases.